An investigation of the impact of an empowerment programme in a Cape Town township - Osuafor, Chikelue Eprhaim (University of the Western Cape, 2016)
Magister Artium (Development Studies) - MA(DVS) === The concept of empowerment has become a mantra in the development discourse as a result of the redefinition of development to entail building the capacity of the people to effect change in their lives. This study is an attempt to provide insight into the impact of empowerment activity of Zonkee Community Development Centre on the participants. Using a combination of qualitative and quantitative research method the study illuminated on the aim and objectives of the study. The World Bank empowerment framework guided the collection of data and the data was analysed in relation to the study aim and objectives. The study findings indicate that Zonkee Community Development Centre through its activity endowed and increased different resource base of the participants and subsequently their individual growth and development. More importantly, the resources they were endowed with aided their ability to make choices and decisions that reflect their value and interest. Furthermore, the findings of the study shows that access to resources which include material and development of sense of self is indispensable for empowerment to take place. In other words power over resources without power within will fall short of bringing about requisite empowerment experience. Nevertheless, the findings point to the complexity of empowerment and unpredictability of empowerment outcomes with regards to choice making. The findings of the study in its entirety indicate that empowerment efforts by civil society group have the potential to diminish sense of powerlessness and enhance capacity of the poor to control their lives.